Long-term continuous corrosion of 316L stainless steel by Streptococcus mutans in simulated oral environment - Zhang, Xiaodong; Liu, Yao; Chen, Guoxian; Bai, Shuai; Li, Zhong; Wang, Fuhui; Xu, Dake (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe widespread application of metallic biomaterials in oral healthcare has raised increasing concerns regarding their long-term corrosion behavior under complex microbial environments, which remains insufficiently understood.MethodsA 90-day anaerobic experimental system was established by inoculating Streptococcus mutans in artificial saliva. The biofilm formation, electrochemical properties, surface corrosion morphology, and product evolution on 316L stainless steel were monitored using SEM, CLSM, electrochemical analysis (OCP, LPR, EIS), AFM, and XPS.ResultsS. mutans formed a dense biofilm on the material surface with a maximum thickness of 88.1 ± 9.0 μm. Compared to the sterile control, the corrosion current density in the experimental group increased by approximately 295-fold, with a maximum pit depth of 5.3 μm. A notable reduction in the content of protective Cr2O3 and NiO within the passive film was observed.DiscussionS. mutans accelerates pitting corrosion through a “biofilm barrier + localized acid production” mechanism that disrupts the passive film. The long-term corrosion effects are substantially more severe than those observed in short-term experiments.